2022
DOI: 10.24815/jipi.v6i1.22721
|View full text |Cite
|
Sign up to set email alerts
|

Integrasi STEM-Problem Based Learning melalui Daring Terhadap Keterampilan Berpikir Kritis Mahasiswa Pendidikan Biologi

Abstract: The development of technology and information in the 21st century supports the implementation of online learning during the pandemic. The learning process that uses the right approach and learning model will be more effective when combined with the use of technology. The purpose of this study was to determine the effect of STEM-PBL integration through online learning on the critical thinking skills of biology education students. The research was conducted on students of the Biology Education Program in Unismuh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
0
5
0
2
Order By: Relevance
“…PBL is able to increase student interest in learning activities (Nizarullah, et al, 2017). The problems presented in this PBL model are real or authentic problems that occur in real life (Anggraini, et al, 2022;Fadhilah, et al, 2022). Through this study, researchers found that students' interest in learning biochemistry using the PBL model and using the integrated sacffolding PBL model had differences.…”
Section: Resultsmentioning
confidence: 80%
“…PBL is able to increase student interest in learning activities (Nizarullah, et al, 2017). The problems presented in this PBL model are real or authentic problems that occur in real life (Anggraini, et al, 2022;Fadhilah, et al, 2022). Through this study, researchers found that students' interest in learning biochemistry using the PBL model and using the integrated sacffolding PBL model had differences.…”
Section: Resultsmentioning
confidence: 80%
“…An encyclopedia with content that is fresh and relevant to everyday life awakens students' interest in studying it. The motivation that arises to study floral diversity material can trigger critical thinking skills (Fadhilah et al, 2022;Suparya, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Pembelajaran STEM secara signifikan meningkatkan pengetahuan keberlanjutan (sustainability knowledge) (Craig et al, 2022) Pembelajaran dengan pendekatan STEM berpengaruh positif terhadap keterampilan berpikir kritis, kreatif, dan pemecahan masalah (Alifa et al, 2018), (Ismayani, 2016), (Dywan & Airlanda, 2020), (Sukmawijaya et al, 2019), (Widana & Septiari, 2021), (Mawarni & Sani, 2020), (Octaviyani et al, 2020), (Santoso & Arif, 2021), (Fadhilah et al, 2022), (Ananda & Dasna, 2019), (Wastiti & Sulur, 2020), (Lukitawanti et al, 2020), (Nurazmi & Bancong, 2021) Aspek Psikomotor…”
Section: Mengacu Kepada Manfaat Aspek Kognitifunclassified